Effectiveness of a BHV-1/BEFV bivalent vaccine against bovine herpesvirus type 1 infection in cattle. (December 2016) - Chung, Yao-Chi; Shen, Hsiu-Yen; Cheng, Li-Ting; Liu, Shyh-Shyan; Chu, Chun-Yen
Abstract: Bovine herpesvirus type 1 (BHV-1) causes acute febrile respiratory diseases (infectious bovine rhinotracheitis, IBR), decreased milk production, weight loss and abortion. Bovine ephemeral fever virus (BEFV) causes acute febrile respiratory disease, with pulmonary emphysema and pulmonary edema as the main signs. These viruses infect domesticated herds and lead to significant economic losses. In our previous study, an inactivated BHV-1 and BEFV bivalent vaccine was formulated with water-in-oil-in-water adjuvant, and vaccine efficacy was evaluated in guinea pigs. In this study, we evaluated the efficacy of the bivalent vaccine in cattle. Results showed that immunized cattle had a significantly higher level of total anti-BHV-1 antibody response (S/P ratio of 12.7) than the control group (S/P ratio of 0.07) 32 weeks post-vaccination. The immunized group also showed higher neutralizing antibody levels against BHV-1 (SN = 2 3.8 ) and BEFV (SN = 2 4.6 ) than the control group (SN < 2) 4 to 32 weeks post-vaccination ( p  < 0.05). In a BHV-1 challenge experiment, immunized cattle showed low virus shedding (10 1.2  TCID50 /mL) and a significant reduction in pathological lesion scores ( p  < 0.01). In conclusion, the BHV-1 + BEFV + w/o/w vaccine not only improved long-term antibody immune response but also significantly reduced clinical signs in a BHV-1 challenge experiment. Our approach may be feasible for developing an effective vaccine against bovine herpesvirus type 1 and bovine ephemeral fever virus. Highlights: BHV-1 and BEFV were formulated with w/o/w adjuvant as a bivalent vaccine. The inactivated bivalent vaccine induced anti-BHV-1 antibody in cattle. In a challenge test, immunized cattle showed low BHV-1 shedding (10 1.2  TCID50 /mL). Vaccine reduced pathological lesion scores in a BHV-1 challenge experiment ( p  < 0.01).